2023
DOI: 10.1111/kykl.12322
|View full text |Cite
|
Sign up to set email alerts
|

Can television reduce xenophobia? The case of East Germany

Abstract: Can television have a mitigating effect on xenophobia? To explore this question, we investigate a natural experiment in which individuals in some regions of East Germany could not—due to their geographic location—consume West German television until 1989. By analyzing survey data from the periods before and after German reunification, we provide evidence that individuals who received West German television during the GDR period and were thus more frequently exposed to foreign media have developed less xenophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…In a seminal study, Jensen and Oster (2009) argue that the spread of cable television in India provided information about the world and the ways that others lead their lives and show that the spread of this technology led to less support for the idea that domestic violence is acceptable. In a similar vein, Hornuf et al (2023) find that exposure to West German television reduces xenophobia in those born in the former East Germany and the level of hate crimes against refugees. Smartphone technology resembles the cable television rollout studied by Jensen and Oster (2009) in terms of providing access to information and the experiences of others but also offers scope for conversations and educational opportunities.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In a seminal study, Jensen and Oster (2009) argue that the spread of cable television in India provided information about the world and the ways that others lead their lives and show that the spread of this technology led to less support for the idea that domestic violence is acceptable. In a similar vein, Hornuf et al (2023) find that exposure to West German television reduces xenophobia in those born in the former East Germany and the level of hate crimes against refugees. Smartphone technology resembles the cable television rollout studied by Jensen and Oster (2009) in terms of providing access to information and the experiences of others but also offers scope for conversations and educational opportunities.…”
Section: Introductionmentioning
confidence: 80%
“…In addition to their own results linking exposure to cable television to changes attitudes and behaviours related to domestic violence (Jensen & Oster, 2009), they point to studies linking television exposure in Muslim countries to attitudes towards the West (Gentzkow & Shapiro, 2004) and to voting behaviour in the United States of America (DellaVigna & Kaplan, 2007). To this, we can add recent work linking exposure to television to reductions in xenophobia and racism (Hornuf et al, 2023).…”
Section: Smartphones and Attitudes To Domestic Violencementioning
confidence: 99%
“…Overall, we argue that the reception of West TV gave certain East Germans the opportunity to access free and democratic West TV, while others had to solely rely on the news they received from the controlled and censored GDR TV. 13 This setting was first exploited by Bursztyn and Cantoni (2016) for the investigation of consumption behavior and used many times later on (as a determinant of success in life (Hennighausen (2015)), voting behavior (Hornuf et al (2020)), or fertility (Bönisch and Hyll (2015)). Importantly, this literature established the regionally different receptions of West German TV across East German regions as a reliable identification strategy.…”
Section: Historical Background and Identification Strategiesmentioning
confidence: 99%
“…West TV (Bursztyn and Cantoni (2016)) 7 . From this, a large literature followed this identification strategy and showed that East Germans with access to West TV are more likely to believe that effort rather than luck determines success in life (Hennighausen (2015)), are less likely to vote for right-wing parties (Hornuf et al (2020)), show lower levels of fertility (Bönisch and Hyll (2015)), a higher probability to become entrepreneurs (Slavtchev and Wyrwich (2017)) and higher levels of consumption aspirations (Hyll and Schneider (2013)). At the regional level, East German regions with access to West TV display lower rates of violent crime and sex crime, but more fraud (Friehe et al (2018)) and, similar to findings at the individual level, have lower vote shares for the extreme left and right-wing parties ).…”
mentioning
confidence: 99%